2007
DOI: 10.1002/ibd.20131
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab and the risk of latent viruses reactivation in active Crohnʼs disease

Abstract: Our results support the safety of short-term infliximab treatment with respect to latent virus reactivation. The long-term effects of infliximab, particularly for the issue of lymphoproliferative disorders, warrants further studies with larger populations, but so far data are reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 50 publications
1
63
1
1
Order By: Relevance
“…Crohn's disease, infliximab therapy did not appear to be associated with JCV activation (72). In addition, a trial in 146 patients with relapsing-remitting MS demonstrated that treatment with IFN beta as monotherapy did not appear to have any effect on active replication of JCV (73), whereas another study in a similar patient group showed that treatment with IFN beta could lead to a reduction in JCV DNA levels in the peripheral blood (74).…”
Section: Polyomavirusmentioning
confidence: 99%
“…Crohn's disease, infliximab therapy did not appear to be associated with JCV activation (72). In addition, a trial in 146 patients with relapsing-remitting MS demonstrated that treatment with IFN beta as monotherapy did not appear to have any effect on active replication of JCV (73), whereas another study in a similar patient group showed that treatment with IFN beta could lead to a reduction in JCV DNA levels in the peripheral blood (74).…”
Section: Polyomavirusmentioning
confidence: 99%
“…CMV serology was positive in 70.0% of samples collected before IFX infusions in consecutive CD patients, indicating latent viral presence. CMV replication and reactivation was not observed (201). CMV was not detected in a pediatric IBD sample treated with biologicals or conventional therapies for over 12 months (202).…”
Section: Hepatitis C Virus Infectionmentioning
confidence: 85%
“…No patient became positive for HHV-6, HHV-7 and HHV-8 in blood samples at any point in a sample of 60 consecutive CD patients treated with IFX (201). HHV-6 was not detected in urine, serum or peripheral blood mononucleated cells in a pediatric IBD cohort treated with biologicals or conventional therapies for over 12 months (202).…”
Section: Other Members Of the Herpes Virus Familymentioning
confidence: 90%
See 2 more Smart Citations